Energy pathways associated with sustained spermatozoon motility in the endangered Siberian sturgeon Acipenser baerii - Rahi, Deepali; Dzyuba, Borys; Xin, Miaomiao; Cheng, Yu; Dzyuba, Viktoriya (Journal of fish biology, 2020)
Sturgeon spermatozoa are unique for their sustained motility. We investigated the relative importance of bioenergetic pathways in the energy supply of Siberian sturgeon Acipenser baerii spermatozoa during motile and immotile states. Spermatozoon motility and oxygen consumption rate (OCR) were analysed following exposure to inhibitors of oxidative phosphorylation (sodium azide, NaN3 ), glycolysis (2-deoxy-D-glucose, DOG) and β-oxidation of fatty acids (sodium fluoride, NaF), and to an uncoupler of oxidative phosphorylation (carbonyl cyanide m-chlorophenyl hydrazine, CCCP). No significant difference in curvilinear velocity was observed after addition of these reagents to activation medium (AM) or nonactivation medium (NAM) for incubation. Incubation of spermatozoa in NAM containing CCCP or NaN3 resulted in significantly decreased motility duration compared to controls. The OCR of sturgeon spermatozoa in AM (11.9 ± 1.4 nmol O2 min-1 (109  spz)-1 ) was significantly higher than in NAM (8.2 ± 1.5 nmol O2 min-1 (109  spz)-1 ). The OCR significantly declined with addition of NaN3 to AM and NAM. No significant difference in motility parameters or OCR was observed with NaF or DOG. These results suggest active oxidative phosphorylation in both immotile and motile spermatozoa. Nevertheless, mitochondrial respiration occurring during motility is not sufficient to meet the high energy demands, and the energy required for sustained motility of Siberian sturgeon spermatozoa is derived from adenosine triphosphate accumulated during the quiescent state.
Keywords: Spermatozoa; Animals; mitochondrie; energetický metabolismus; Oxygen Consumption; Sperm Motility; mužské pohlaví; zvířata; Fishes; Adenosine Triphosphate; Male; Energy Metabolism; spermie; Mitochondria; adenosintrifosfát; spotřeba kyslíku; motilita spermií; ryby